Identity Design and Identities Exhibited in Social Networks: A Review Based on Instagram Influencers - Sönmez, Mehmet Ferhat (IGI Global, 2022)
Identity emerges as a flexible, multidimensional, variable, and slippery concept that cannot be defined through the processes of discussion and understanding. The new construction area of this concept, which is regarded as a process constructed on the social plane, is the social networking platforms. This is because these platforms are the most common communication environments where people and their lifestyles are presented to the outside world, in addition to the cheap and rapid satisfaction of their needs for information and entertainment. Face-to-face communication and language practices are not sufficient enough in the identity presentation anymore. Individuals choose to design and update their identities through social networks and to perform an image-based identity manifestation. This chapter examines how identity was established and manifested through social networks, and analyzes the identities the popular people in these networks designed and exhibited © 2022 by IGI Global. All rights reserved.
Keywords: Communication environments; Face-to-face communications; Image-based; New constructions; Social-networking; Social networking (online)